Arabidopsis phospholipase Dβ1 modulates defense responses to bacterial and fungal pathogens - Zhao, Jian; Devaiah, Shivakumar P.; Wang, Cunxi; Welti, Ruth; Wang, Xuemin (My University, 2013)
[1] Pathogen infection of higher plants often induces rapid production of phosphatidic acid (PA) and changes in lipid profiles, but the enzymatic basis and the function of the lipid change in pathogen–plant interactions are not well understood. [2] Infection of phospholipase D β1 (PLDβ1)-deficient plants by Pseudomonas syringae tomato pv. DC3000 (Pst DC30000) resulted in less bacterial growth than in wild-type plants, and the effect was more profound in virulent Pst DC3000 than avirulent Pst DC3000 (carrying the avirulence gene avrRpt2) infection. The expression levels of salicylic acid (SA)-inducible genes were higher, but those inducible by jasmonic acid (JA) showed lower expression in PLDβ1 mutants than in wild-type plants. [3] However, PLDβ1-deficient plants were more susceptible than wild-type plants to the fungus Botrytis cinerea. The PLDβ1-deficient plants had lower levels of PA, JA and JA-related defense gene expression after B. cinerea inoculation. [4] PLDβ1 plays a positive role in pathogen-induced JA production and plant resistance to the necrotrophic fungal pathogen B. cinerea, but a negative role in the SA-dependent signaling pathway and plant tolerance to infection with biotrophic Pst DC3000. PLDβ1 is responsible for most of the increase in PA production in response to necrotrophic B. cinerea and virulent Pst DC3000 infection, but contributes less to avirulent Pst DC3000 (avrRpt2)-induced PA production.
Keywords: Botrytis cinerea; Pseudomonas syringae; Arabidopsis thaliana; Pathogeneses; Phosphatidic acid; Lysophospholipids; Lipid signaling